Pemodelan Menggunakan Software Plaxis Untuk Simulasi Daya Dukung Fondasi Bored Pile - Nur Syintyiah Rachmah (Jurnal Vokasi Teknik Sipil, 2024)
The foundation of a drill pile or bored pile is used to support a building structure by drilling a hole into the ground and filling it with steel reinforcement and concrete. Evaluation of the strength of the supporting capacity of a bored pile foundation is important in the design and construction process, to ensure that the foundation can bear the load of the structure to be placed on it. The study used the Plaxis 2D software to simulate the support strength of the bored pile foundation, the Luciano Decourt method, and the Reese and Wright method to determine the comparison of the maximum support strength values. The results of this study show that the support power value obtained with the Reese and Wright method is closer to the support force result using the 2D Plaxis. From the third method calculations, the Qult value difference between the Plaxis 2D method and the Luciano Decourt method is -469.73 kN or -32.8% for data 1, -666.56 kN, or -36.7% for data 2, and -407.24 kN and -12.1% for data 3. For the differential between the Plaxis 2D method and the Reese and Wright method, the result was 0.63 kN or 0.1% for data 1, 78,58 kN, or 7.3% for data 2, and -80,64 kN (or -2.7% for data 3).